TALES OF SCIENCE: THE TRANSFORMATIVE POWER OF FOLKLORE IN HIGHER EDUCATION BIOLOGY - Pardosi, Sri Masnita; Mubarokah, Nadia; Fairuz, Tariza; Rangkuty, Sailana Mira (Universitas Negeri Medan, 2025)
This research investigates the effectiveness of integrating folklore narratives into biology education within higher education as a pedagogical strategy to enhance scientific literacy and conceptual understanding. The study explores how folklore-based learning can improve students’ comprehension of core biological concepts, including ecology, genetics, and biodiversity, by connecting abstract scientific principles to relatable cultural contexts. Through the analysis of various folklore traditions and their implicit biological principles, this study demonstrates the potential of these narratives to bridge the gap between theoretical biology and real-world applications. An experimental study was conducted to evaluate the impact of folklore-based instruction on student learning outcomes compared to traditional teaching methods. Results indicate significant improvements in student engagement, critical thinking skills, and conceptual understanding of biology among higher education students exposed to folklore-integrated lessons. This approach not only promotes cultural awareness and appreciation for traditional knowledge but also stimulates scientific discourse and problem-solving abilities. This study advocates for the incorporation of local folklore into science curricula within higher education to enrich student learning experiences and foster a deeper, more nuanced understanding of biology and its societal relevance, ultimately contributing to improved scientific literacy.